Synergistic effects of environmental credit evaluation and emissions trading in promoting enterprise carbon reduction - Wang, Jingyuan; Luo, Qingfeng (Frontiers in Environmental Science, 2025)
This study empirically analyzes the synergistic effects of China’s environmental credit evaluation system and carbon emissions trading policy on enterprise carbon emission intensity. Employing a difference-in-differences approach on 27,718 firm-year observations from China’s A-share listed companies over the period 2007 to 2021, the findings indicate that the dual pilot policy (DPP) significantly reduced carbon emission intensity by approximately 0.184 units. This impact is markedly stronger than that observed when either policy is implemented individually, demonstrating a clear synergistic effect. Mechanism tests reveal that the DPP primarily reduces carbon emission intensity through supervisory mechanisms involving multiple governance bodies, such as market oversight, media scrutiny, and public supervision. Furthermore, the DPP drives reductions in carbon emission intensity through corporate behavior adjustment mechanisms, including increasing environmental investment, promoting green technological innovation, optimizing energy consumption, and enhancing green development efficiency. The results of the heterogeneity analysis indicate that the DPP has a greater impact on reducing emissions in non-state-owned enterprises, mature enterprises, high-carbon and high-pollution industries. This study fills a gap in empirical research on the synergistic effects of the environmental credit evaluation system and the carbon emissions trading pilot policy, providing theoretical support and practical reference for optimizing environmental policy and facilitating corporate low-carbon transition.